Integrating pre-purchase affect in product concept development. (17th December 2007) - Seva, Rosemary R.; Helander, Martin G.; Duh, Henry Been-Lirn
The Pre-purchase Affect Model (PAM) was developed. It predicts how product criteria for purchase may engender affect. A field survey was conducted to determine what criteria consumers use to purchase electronic products and items of clothing. A total of 23 and 21 criteria were identified for buying clothing and electronic products, respectively. There were 11 types of criteria for clothes and nine for electronic products. The criteria were compared with the product attributes. If there was a match pre-purchase affect resulted. The use of the model will help define design attributes that are capable of eliciting affect.